Transcutaneous electrical acupoint stimulation alleviates cerebral ischemic injury through the TLR4/MyD88/NF-κ B pathway - Wu, Linyu; Tan, Zixuan; Su, Lei; Dong, Fang; Xu, Guangyu; Zhang, Feng (Frontiers in Cellular Neuroscience, 2024)
This study was to explore whether transcutaneous electrical acupoint stimulation (TEAS) treatment could mediate inflammation, apoptosis, and pyroptosis of neuronal cells and microglia activation through the TLR4/MyD88/NF-κB pathway in the early stage of ischemic stroke. TEAS treatment at Baihui (GV20) and Hegu (LI4) acupoints of the affected limb was administered at 24, 48, and 72 hours following middle cerebral artery occlusion/reperfusion (MCAO/R), with lasting for 30 minutes each time. Neurological impairment scores were assessed 2 hours and 72 hours after ischemia/reperfusion (I/R). TTC staining was used to evaluate the volume of brain infarction. The histopathologic changes of hippocampus were detected by H&E staining. WB analysis was performed to assess the levels of TLR4, MyD88, p-NF-κB p65/NF-κB p65, and inflammation, apoptosis, pyroptosis-related proteins. TLR4 expression was measured using immunohistochemistry. The expression of inflammation-related proteins was also measured using ELISA. Immunofluorescence was used to detect the expression level of Iba1. Our findings demonstrated that TEAS intervention after I/R improved neurological function, reduced the volume of brain infarction, and mitigated pathological damage. Moreover, TEAS reduced the levels of TLR4, MyD88, p-NF-κB p65/NF-κB p65, TNF-α, IL-6, Bax, NLRP3, cleaved caspase-1/pro caspase-1, IL-1β, IL-18, GSDMD, and Iba1 while enhancing Bcl-2 expression. Moreover, the protective effects of TEAS could be counteracted by lipopolysaccharide (LPS, a TLR4 agonist). In conclusion, TEAS can reduce cerebral damage and suppress inflammation, cell death, and microglia activation after ischemic stroke via inhibiting the TLR4/MyD88/NF-κB pathway.